Flight control of tethered kites in autonomous pumping cycles for airborne wind energy. (July 2015) - Erhard, Michael; Strauch, Hans
Abstract: Energy harvesting based on tethered kites benefits from exploiting higher wind speeds at higher altitudes. The setup considered in this paper is based on a pumping cycle. It generates energy by winching out at high tether forces, driving an electrical generator while flying crosswind. Then it winches in at a stationary neutral position, thus leaving a net amount of generated energy. The focus of this paper is put on the flight control design, which implements an accurate direction control towards target points and allows for a flight with an eight-down pattern. An extended overview on the control system approach, as well as details of each element of the flight controller, is presented. The control architecture is motivated by a simple, yet comprehensive model for the kite dynamics. In addition, winch strategies based on an optimization scheme are presented. In order to demonstrate the real world functionality of the presented algorithms, flight data from a fully automated pumping-cycle operation of a small-scale prototype are given. The setup is based on a 30 m 2 kite linked to a ground-based 50 kW electrical motor/generator by a single line. Abstract : Graphical abstract: Abstract : Highlights: Energy generation by flight and winch control in pumping cycles. Control design based on a simple model for tethered kite dynamics. Overview on flight control setup and detailed description of respective elements. Pattern control by target points and winch strategies for different cycle phases. Discussion of data from a 30 m 2 kite linked to a ground-based 50 kW motor/generator.